1983
DOI: 10.1111/j.0954-6820.1983.tb03685.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Effects of Noise

Abstract: Thirteen patients with mild essential hypertension, mean age 44 years (range 21–59), were studied during “stress” before and after postsynaptic α‐adrenoceptor blockade and combined postsynaptic α‐ and non‐selective β‐adrenoceptor blockade. Loud broad band noise (100 dBA for 10 min) was used as the stress stimulus. Exposure to noise caused a significant increase in systolic (7%, p<0.05), diastolic (9%, p<0.01) and mean arterial pressure (6%, p<0.01). The blood pressure elevation was caused by an increase in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 17 publications
2
14
0
2
Order By: Relevance
“…The elevations of ambulatory SBP and DBP caused by a 1-dBA increase in the 24-h average noise exposure among the hypertensive workers during the working and nonworking days supported the results in an experimental study that exposure to 100 dBA for 10 min caused the significant elevations of resting SBP and DBP among 13 patients with mild essential hypertension [26]. However, the differences in the DBP between the hypertensive and normotensive groups during sleep (with a maximum value of 0.06 mmHg in DBP) were obviously lower than those in the SBP (with a maximum value of 0.22 mmHg in SBP).…”
Section: Discussionsupporting
confidence: 72%
“…The elevations of ambulatory SBP and DBP caused by a 1-dBA increase in the 24-h average noise exposure among the hypertensive workers during the working and nonworking days supported the results in an experimental study that exposure to 100 dBA for 10 min caused the significant elevations of resting SBP and DBP among 13 patients with mild essential hypertension [26]. However, the differences in the DBP between the hypertensive and normotensive groups during sleep (with a maximum value of 0.06 mmHg in DBP) were obviously lower than those in the SBP (with a maximum value of 0.22 mmHg in SBP).…”
Section: Discussionsupporting
confidence: 72%
“…In the latter instance, it was suggested that the main effect of noise was to disrupt normal hormone release patterns, such that the daily peak occurred later. Increases in noradrenaline levels have been reported for humans (Andrén et al. 1983), rats (Lenzi et al.…”
Section: The Neuroendocrine Systemmentioning
confidence: 96%
“…As with research on the HPA axis, the bulk of cardiovascular studies have focused on humans, rats and mice. Among humans, exposure to loud noise (both temporary and long‐term), is associated with increases in systolic, diastolic and main arterial pressures, leading to an increase in total peripheral resistance to blood flow (Andrén et al. 1983).…”
Section: Cardiovascular Healthmentioning
confidence: 99%
“…Noise, defined as undesirable sound, is unknown to be a stress stimulus (Mondal, 2013) that can produce acute blood pressure (BP) elevation in animals (Baudrie et al, 2001) and humans in laboratory or occupational settings (Andren et al, 1983). Noise is most widely spread pollutant in work environment and living environments (Mondal and Ghatak, 2014;Tomei et al, 2000).…”
Section: Introductionmentioning
confidence: 99%